Development of an Adventure Game Using Construct 3: The Lost: Roux's Escape - Ramadani, Dinda Putri; Wibisono, Praditya Oktanza Djaduk; Prayitno; Ismail, Muhammad (MASE - Media Applied and Engineering, 2025)
Adventure games include some of the most popular genres in the gaming industry, with rich narrative arcs and interactive game play. In this research study, the 2D adventure game is designed and developed by using a game engine called Construct 3, which is an easy-to-use and powerful game development application. This study encompasses the design and execution of game mechanics, narrative and graphical elements to provide an immersive experience. We employed an iterative design methodology, which included game prototyping, testing and refinement. The project was assessed in regard to vitality based on gameplay smoothness, user engagement, visuals and received positive feedback from initial testers. Overall, the results point to the successful use of Construct 3 as a development tool, especially for indie developers and educators looking to design gamified learning environments. Overall, this study shows that Construct 3 can help in making game development more accessible to a broader audience, ultimately leading to a more balanced domain of creative outputs in the industry.